Удмуртские народные мифы и легенды - Кралина Надежда Петровна (Удмуртия, 2016)
Экземпляры: (20201014) / Инвентарный номер: 41563 / Цена: 7000.00 / Сис.шифр: 82.3(2=664.1) / Авт.знак: У 30 / ГРНТИ: 17 / ББК: 82.3(2=664.1)